(untitled) (Mustansiria Dental Journal, 2018)
This study was done to determine the possible number of repair that can be carried out on the same light-cured microfilled composite resin (Helioprogress, vivadent, Germany). 40 specimens were prepared, stored in deionized distilled water at 37°C for 24 hours and divided into 4 groups. Group 1: The repair procedure done once. Group 2: The repair procedure done twice. Group 3: The repair procedure done for three times. Group 4: The repair procedure done for four times. All the specimens stored in deionized distilled water at 37°C for 24 hours before testing. A universal zwick testing machine with a special designed chisel was used to evaluate the shear bond strength of the repaired composite resin. The results showed reduction in mean shear bond strength value from group 1 to group 4, furthermore a significant difference was found between group 1 Vs group 3 and group 1 Vs group 4.